SOURCE ROCK ANALYSIS THROUGH MATURATION MODELLING UTILIZING TRANSFORMATION RATIO (TR) METHOD WITHIN THE NORTH KAKAP AREA, WEST NATUNA BASIN, INDONESIA - CHALIK, MU'ADZ
Recent detailed mapping was used to revise the structural, stratigraphic and geochemical framework of the North Kakap Block and surrounded areas. Geochemical studies indicate that the Kakap oils were generated from lacustrine Type I kerogen. This kerogen occurs within Eocene to Oligocene lacustrine shale sequences of the Benua/Lama Formation, and it may also be present in lacustrine shales of the lowermost part of Lower Gabus sequences. The maturation modelling was performed using the BasinMod I-D For Windows software program. The main assumptions and input parameters, single plot analyses for the wells, geochemical data diagrams and stratigraphic determination for burial history are derived from geochemical analyses of well sampels from Pyrolysis-GC data, thermal history, and structural development. The transformation ratio (TR) method and thermal history have been used in maturation modelling technics to identify the source rocks and thermal maturity within the area. Source rock maturation modelling shows that a kitchen area exists now for the Benua/Lama interval (1) to the west of the North Kakap Block and (2) extending east from the easternmost part of the North Kakap. In the west, however, due to long migration distance and complex faulting resulting in unfavourable juxtapositioning of carrier beds across faults. It is postulated that the Benua/Lama have charged the known oil accumulations in the western part of North Kakap. The maturation modelling using transformation ratio indicates that in the eastern part of North Kakap there are three models of mature source rocks level exist; the present day, the 9.4 mya and the 23.2 mya. A present-day Benua/Lama oil kitchen area has been defined within the eastern part of North Kakap Block underlies the known prospects in the KB half graben area. Lateral migration from this deep oil kitchen area is over short distance with vertical migration via faults being the principle charge mechanism for the overlying oil accumulations. The results of this maturation modelling also have led to the conclusion that the Benua/Lama lacustrine sequences of Eocene to Early Oligocene age is the most likely source for the known accumulations within the North Kakap.